Checking activities related to the control of prescriptions - legal approach - Michał Jachowicz; Michał Kobylarz (Polish Pharmaceutical Society, 2022)
The subject of this article is the analysis of legal conditions regarding prescriptions control, carried out by National Health Fund on the basis of the Act of May 12, 2011, on reimbursement of medicines, foodstuffs for particular nutritional uses and medical devices, as well as the Act of August 27, 2004 on healthcare services financed from public funds - with particular reference to the distinction between a control and activity qualified as checking activities. One of the most important differences between a control and activity qualified as checking activities, is that on the ground of the control procedure the inspected entity disposes of legal remedies, and on the other hand the inspected entity doesn't dispose such legal remedies in case of checking activities - the material scope of which is only slightly reduced in relation to control. The indicated divergence may result in the excessive application by the controlling entity the power to perform checking activities as mechanisms much preferable and easier than the control requiring a more complex and formal procedure. Defending the view that the National Health Fund is obliged to apply the in dubio pro libertate principle and resolve doubts as to the content of a legal norm in favour of the entrepreneur, it should be recognised that the National Health Fund is obliged to apply the interpretation of the law, according to which the result of control activities does not in itself constitute the basis for the application of legal sanctions. The above view is not only justified by the statutory provisions, but is significantly reinforced by Art. 2 of the Constitution of the Republic of Poland expressing the principle of a democratic state governed by the rule of law. The exercise by the National Health Fund of control competences on the basis of the in dubio pro libertate principle seems to be expected both due to the Fund's obligation to implement the principle of trust, but also due to the obligation to act on the basis and within the limits of the law, understood as a system of legal rules on specific relationships and requiring a comprehensive interpretation based on a complex mechanism of rules interpretation for the correct application.